INDIRECT COST ANALYSIS OF THE CONSTRUCTION PROJECT OF SPORTS FACILITIES IN KANOR SUB-DISTRICT, BOJONEGORO DISTRICT WITH LINEAR REGRESSION METHOD - Zuhri, Syaefuddin; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
The calculation of indirect costs carried out by contractors so far has no reference or there is no standardized design to be a benchmark. For this reason, researchers will analyze the primary and secondary data of this study to determine the indirect costs of direct costs or against the contractors' contracts. This study analyzes the amount of indirect costs in the Kanor District Sports Facilities Development project of Bojonegoro Regency and looks for a relationship between indirect costs and bid prices with time performance on the Kanor District Sports Facilities Development project of Bojonegoro Regency. This research method uses data processing and indirect cost RAB making. and using analysis methods with linear regression statistical analysis. Indirect costs in the Kanor District Sports Facilities Development project are allocated to 4 (four) main things, namely tax and insurance costs (61.49%), risk costs (7.21%), and overhead costs (8.62%), general costs (8.325) quality costs 4.36%) where the percentage is calculated from the total amount of indirect costs. From the linear regression analysis it can be concluded that indirect costs affect the project work time. Bid price has no effect on project work time. Indirect costs and bid prices affect the time of work.